Vector Competence of Aedes aegypti from São Tomé and Príncipe for West Nile Virus Transmission - Rafael Marmé; Filipe Tomaz; Carla A. Sousa; João Pinto; Gregory C. Lanzaro; Ricardo Parreira; Gonçalo Seixas (Microorganisms, 2024)
The global distribution of Aedes aegypti mosquitoes, particularly in tropical regions, poses a significant public health risk due to their apparent ability to transmit arboviruses such as West Nile virus (WNV). This study aimed to evaluate the vector competence of Ae. aegypti from São Tomé and Príncipe (STP) for the transmission of the WNV PT6.39 strain, considering its potential role as a bridge vector in a region where Culex quinquefasciatus would be the main vector. Aedes aegypti mosquitoes were collected, reared, and experimentally infected with WNV, with viral dissemination and transmission potential assessed 7, 14, and 21 days post infection (dpi). The results showed an increasing trend in infection rates, from 5% at 7 dpi to 35% at 21 dpi, with corresponding dissemination rates of 0%, 100%, and 43%. The transmission rates also increased from 0% at 7 dpi to 67% at 21 dpi, with a maximum transmission efficiency of 10% observed at the final time point. Although Ae. aegypti from STP demonstrated the potential to transmit WNV, the overall transmission efficiency remained relatively low. These findings provide necessary insights into the vector competence of Ae. aegypti in this region, highlighting the importance of continued monitoring and targeted vector control measures to mitigate the risk of potential WNV outbreaks.